Dinamika pergeseran Makna Kata Anjir dalam Komunikasi Digital pada Platform TikTok - Sudirman, Rahmayani; siti Masyita Rahmi; Siti Nurfadila Ramadhani; Anita Chandra Dewi (AIJER: Algazali International Journal Of Educational Research, 2025)
Abstrac: This study examines the shift in meaning of the word “anjir” in digital communication on the TikTok platform. The word “anjir” which was originally a variant of a word considered rude, has now undergone a transformation in meaning into a more flexible and contextual expression. Using a qualitative descriptive method with a sociolinguistic approach, this study analyzes the use of the word “anjir” in various contexts on TikTok, including variations in its form and morphological processes. The results of the study show that the word “anjir” has undergone a significant diversification of meaning, no longer solely having a negative connotation, but is used to express expressions, admiration, agreement, annoyance, and various other emotions. In addition, the word “anjir” has also undergone various morphological processes such as clipping and affixation, resulting in variations in form such as “njir”, “anjirr”, “anjer”, and “anjret”. This shift in meaning reflects the social and cultural dynamics among TikTok users, especially the younger generation, and shows how social media platforms facilitate the evolution of language in digital communication. This study contributes to the linguistic understanding of language transformation in the digital age and creativity on how language becomes a means for young generations to express identity and build community in digital spaces.